Severe Hyponatremia with Normokalemia in Pembrolizumab-Lenvatinib Combination Therapy for Metastatic Renal Cell Carcinoma: A Case of Suspected Secondary Adrenal Insufficiency and Clinical Differentials - Devina Ravelia Tiffany Subroto; Steven Jonathan; I Putu Bayu Triguna (HM Publisher, 2026)
The combination of Pembrolizumab and Lenvatinib has become the standard first-line treatment for advanced renal cell carcinoma (RCC). However, the overlapping toxicity profiles of immune checkpoint inhibitors (ICIs) and tyrosine kinase inhibitors (TKIs) create significant diagnostic challenges, particularly regarding electrolyte disturbances. Differentiating ICI-induced secondary adrenal insufficiency from TKI-induced toxicity or syndrome of inappropriate antidiuretic hormone (SIADH) is critical, especially in resource-limited settings where rapid hormonal assays are unavailable. A 67-year-old male with metastatic clear cell RCC presented with confusion, fatigue, and nausea 14 days after initiating palliative Pembrolizumab and Lenvatinib. He had a history of partial nephrectomy and was on Candesartan. Evaluation revealed severe hypotonic hyponatremia (113 mmol/L), acute kidney injury (Creatinine 2.2 mg/dL), and a hypertensive crisis (BP 229/138 mmHg). Notably, despite renal impairment and angiotensin receptor blocker therapy, potassium levels were normal (4.2 mmol/L). The hyponatremia was refractory to 3% hypertonic saline. Suspecting secondary adrenal insufficiency, empiric high-dose corticosteroids were administered, resulting in rapid normalization of serum sodium and resolution of symptoms. In conclusion, in patients receiving ICI-TKI therapy, the specific profile of severe hyponatremia with normokalemia—particularly in the context of renal insufficiency and RAAS blockade—serves as a high-value clinical indicator of preserved mineralocorticoid function. This points toward secondary adrenal insufficiency rather than primary adrenal injury or TKI-induced renal tubular acidosis. This case underscores the utility of deductive physiology in oncology practice.